Composição e atividade sedativa e anestésica do óleo essencial de Aloysia gratissima (Gillies & Hook.) Troncoso (Verbenaceae) em jundiás (Rhamdia quelen) - Benovit, Simone Cristina (2012)
This work was designed to isolate the active compounds responsible for the central activity detected for the essential oil of Aloysia gratissima (EOA) in silver catfish (Rhamdia quelen). The AChE (acetylcholiesterase) activity under the influence of EOA was also investigated. Silver catfish were submitted to anesthesia bath with EOA (90, 300, 450 or 900 mg L-1), their fractions and isolated compounds to determine time of anesthetic induction and recovery. Eugenol (50 mg L-1) was used as positive control. EOA was effective as anesthetic at concentrations of 300 to 900 mg L-1. However, silver catfish presented involuntary muscle contractions during induction and recovery. AChE activity was not inhibited by EOA. The bio-guided fractionation of EOA furnished E-(-)-pinocamphone, (-)-caryophyllene oxide, (-)- guaiol and (+)-spathulenol, which were identified by mass spectrometry (MS), 1H- and 13CNMR. E-(-)-pinocamphone caused the same side effects observed to the EOA. (-)- Caryophyllene oxide, (-)-guaiol and (+)-spathulenol showed only sedative effects at concentrations proportional to those of the constituents in EOA. (-)-Caryophyllene oxide was also sedative in higher concentration (40 mg L-1) than present in EOA while (+)-spathulenol (51.2 mg L-1) promoted deep anesthesia without side effects. EOA showed anesthetic properties, however, should be used with caution in silver catfish due to observed side effects. A higher concentration of (+)-spathulenol, and lower or absent amounts of E-(-)- pinocamphone could contribute to improve the activity of the EO of A. gratissima. (+)- Spathulenol showed potent sedative and anesthetic activities in silver catfish, and could be considered as a promising anesthetic compound.